PHOTOMETRICAL STUDY OF OVERCONTACT BINARY SYSTEM V859Cyg - Panko, E. A.; Sergienko, O. G.; Pomazan, A. V.; Bodryagin, D. V. (Одеські астрономічні публікації, 2016)
Wepresent the results of photometrical research of close binary system V859Cyg with possible period variations. The light curve of the star was constructed using V-band magnitudes, obtainedin 2007, 2009, 2014 years in Kalinenkov Astronomical Observatory of Nikolaev National University (Nikolaev,Ukraine). According our full light curve both eclipsesare partial ,the depths of primary and secondary minima in V–band are 0m,38 and 0m,32 respectively. We found 9 new time minima. However, the standard ephemeris of primary eclipse corresponds to our secondary minimum and vice versa during all observational seasons.We obtained the parameters of binary system from light curve using Binary Maker 3 package. The inclination of orbit of V859 Cyg system is 64,◦5. The temperatures of components are TeffI =7100K, TeffII =6850K and mass ratio is 0.35. Both components are deformed by mutual gravity and overﬁll own Roshe lobes, ﬁllout factor is 0.875 for both stars. Mean radii of components are 0.51 and 0.33 of distance between stars. We attributed V859Cyg as overcontact system with stable period 0,d4050066.